Rb-Sr Geochronology, Geochemistry, and Petrography of Two High Grade Gneisses Found Near Parry Sound, Ontario - Connare, Kevin M. (My University, 1986)
The granulite grade McKellar Gneiss and amphibolite grade Nobel Gneiss have been the subjects of detailed geochronologic, geochemical, and petrographic analyses. The Nobel Gneiss, an amphibolite grade gneiss with an average granite composition, has been dated by the rubidium-strontium (Rb-Sr) whole rock dating method and has yielded an age of 1330 +44 Ma with an initial strontium 87/86 ratio of .7033.
The McKellar Gneiss is a homogeneous mafic granulite with heterogeneous portions, one of which has been dated by the rubidium-strontium whole rock dating method and yielded an age of 1241 +12 Ma with an initial strontium 87/86 ratio of .7034.
The age obtained for the Nobel Gneiss is interpreted as the time of emplacement. The age obtained for the McKellar Gneiss is interpreted as the time of granulite grade metamorphism.
In addition, eight samples from a shear zone which has, in part, been retrograded from granulite facies to amphibolite facies, have also been studied to determine the effects of retrograde metamorphism on the Rb-Sr isotopic system and on the overall chemical and mineralogical system. Analytical results indicate the introduction of water and possible chemical homogenization of the rocks involved in the shearing event.
Title: Rb-Sr Geochronology, Geochemistry, and Petrography of Two High Grade Gneisses Found Near Parry Sound, Ontario, Author: Kevin M. Connare, Location: Thode